Identity Processes and Dynamics in Multi-Ethnic Europe - Westin, Charles; Bastos, José; Dahinden, Janine; Góis, Pedro (IMISCOE Research, 2010)
Globalisation, migration and integration have shaken up identity processes and identity dynamics as never before. But in a post-colonial, multi-ethnic Europe, what is identity? How is it constructed? Identity Processes and Dynamics in Multi-Ethnic Europe endeavours to answer these questions and more. Eleven of the thirteen chapters present empirical case studies from the Basque Country, the Netherlands, Switzerland, the United Kingdom and Portugal - thus resulting in one of the first international volumes to highlight Portugal's diverse and complex migration flows. Transnationalism also takes centre stage in several contributions that survey various types of informal and formal networks in local communities and across national borders. Via American studies, anthropology, cultural studies, ethnology, history, social psychology and sociology, the authors come from an array of disciplines as dynamic as the continent about which they write. This title is available in the OAPEN Library - http://www.oapen.org.